Smart Sensing Technology for Agriculture and Environmental Monitoring - Chandra Mukhopadhyay, Subhas (Lecture Notes in Electrical Engineering, 2012)
The book focuses on the different aspects of sensing technology, i.e. high reliability, adaptability, recalibration, information processing, data fusion, validation and integration of novel and high performance sensors specifically aims to monitor agricultural and environmental parameters.   This book is dedicated to Sensing systems for Agricultural and Environmental Monitoring  offers to variety of users, namely, Master and PhD degree students, researchers, practitioners, especially Agriculture and Environmental engineers. The book will provide an opportunity of a dedicated and a deep approach in order to improve their knowledge in this specific field.